Individualization of work of a student with vision impairment and his psychosocial functioning - Dębska, Agnieszka; Zawadzka, Agnieszka (Journal of Education, Health and Sport, 2018)
Introduction. The sight is of inestimable importance in every child’s process of learning. Lack of eyesight hinders both learning about reality and developing practical skills. Overcoming difficulties and limitations resulting from the loss of vision or serious vision defect requires knowledge about the possibilities of supporting individuals with total vision loss and visual impairment. This requires learning about limitations and physical, psychosocial, orientation and cognitive consequences. Aim. This article deals with theoretical issues related to the individualization of work of a student with vision disability. The aim of the work is to get acquainted with the model of work with a blind student and determine ways to support his education. Presentation of the consequences of visual disability taking into account the psychosocial functioning of people with damaged eyesight has made it possible to approximate the phenomenon of perceptual compensation. The limitations and difficulties of blind or visually impaired students in spatial orientation emphasised the importance of technical support necessary for safe mobility of the blind in both the educational institution and daily situations. Summary. Teachers, vision therapists and tyflopedagogy educators play a special role in developing proper practical skills of the visually impaired. It is extremely important that not only the core curriculum, the curriculum, the assessment principles should be adapted to the student’s individual abilities, but also the psychosocial conditions should allow the student to feel accepted in a peer environment. It is also important to provide appropriate assistance to a visually impaired student in the initial period of his education, because it is of great importance for further efficiency of his work and development.